Developmental duration as an organizer of the evolving mammalian brain: scaling, adaptations, and exceptions. Issue 1 (3rd December 2019) - Finlay, Barbara L.; Huang, Kexin
Abstract: Neurodevelopmental duration plays a central role in the evolution of the retina and neocortex in mammals. In the diurnal primate eye and retina, it is necessary to scale the number of cones versus the number of rods with different exponents to defend their respective functions of spatial acuity and sensitivity in eyes of different sizes. The order of photoreceptor precursor specification, cones specified first, rods second, couples their respective cell numbers at maturity to the kinetics of embryonic stem cell proliferation. Different durations of retinogenesis change the ratio of rods to cones produced so as to defend both functions over a range of eye diameters. In the evolution of nocturnality, the same coupling of photoreceptor specification to neurogenesis is altered to fewer cones and many more rods in nocturnal eyes, by delaying the onset of retinogenesis. Similarly, the neocortex also shows coupling of the specification of laminar position with duration of neurogenesis. Overall, duration of neurogenesis directly predicts neocortex volume in most mammalian clades. In larger brains with longer neocortical neurogenesis, its organization changes progressively, differentiating the frontal pole from the occipital pole in volume of connectivity and number of neurons per unit column. This permits greater, hierarchically organized information abstraction with increasing neocortex volume. Exceptions do exist, however, in species of three separate taxa, marsupials, naked mole rats, and bats, which break the correlation of neurodevelopmental duration and brain size. Naked mole rats and bats both have small brains and unusual longevity, coupled with neurodevelopmental periods characteristic of much bigger‐brained animals, raising the possibility that developmental duration and lifespan have some genetic or mechanistic control in common. The role of duration of development in mediating between the mechanistic levels of construction of retinal and cortical organization, and the different life histories associated with larger brains, such as duration of parental care, learning and overall longevity are discussed. Abstract : A representation of a model which links the normal gradients of neuron number and layering of the neocortex in single species to the differences across multiple species in evolution, via the single parameter of developmental duration. The consequences of extended duration for other sensory and neural systems are considered. Research Highlights: The sequence and duration of cone and rod generation in the primate retina automatically scales the number of each to satisfy the psychophysical requirements of large eyes. The cortex progressively changes its organization to permit greater, hierarchically organized information abstraction with increasing size. The naked mole rat, and bats have small brains but extreme longevity, interestingly coupled with a duration of neurodevelopment associated with much larger brains.